The response of surface-borehole azimuthal induced polarization in axial electrical anisotropic media - Zhou, Lei; Chen, Tianjun; Zhang, Jun-Ke; Chen, Guanda; Wang, Xinyu; Mao, Yurong; Yan, Liangjun (Frontiers in Earth Science, 2025)
The subsurface media in reality are often electrically anisotropic, thus it is necessary to investigate the response characteristics of surface-borehole Azimuthal induced polarization (SBIP) in principal axis anisotropic media. This paper presents a 3D forward modeling of SBIP in principal axis anisotropic media by incorporating tensor conductivity of anisotropic formations into the secondary potential method and equivalent resistivity theory, with numerical implementation through the finite element method. The accuracy of the forward algorithm was validated using an isotropic spherical model in borehole-surface configuration. By constructing multiple sets of three-dimensional (3D) principal-axis anisotropic models, we analyze the response characteristics of apparent resistivity and apparent polarizability under varying excitation azimuths. The simulation results demonstrate that the apparent resistivity and apparent polarizability exhibit the highest sensitivity to anisotropic variations along the Z-axis of the anomalous body, followed by the X-axis, while the Y-axis shows the least sensitivity. This study is not only helpful to improve the theoretical basis of azimuthal induced polarization method when the formation is electrically an-isotropic, but also has certain reference value for subsequent data processing and interpretation.